(untitled) (gjstudies, 2025)
This research investigates the determinants of audit quality within highly regulated financial industries, moving beyond traditional compliance-centric modelsto propose a novel, dynamic framework. While existing literature predominantlyfocuses on auditor independence, technical competence, and regulatory adherence,this study introduces the concept of ’Regulatory Intelligence Quotient’ (RIQ) asa critical, yet previously unquantified, determinant. RIQ encompasses an auditfirm’s systemic capacity to not only interpret complex, evolving regulations butto anticipate regulatory shifts and integrate this foresight into audit planning andexecution. The methodology employs a mixed-methods approach, combining alongitudinal analysis of audit outcomes in the banking, insurance, and securitiessectors from 2015 to 2023 with qualitative insights derived from in-depth interviews with Chief Audit Executives, regulators, and fintech innovators. We developand validate a multi-dimensional RIQ index, measuring components such as predictive regulatory analytics adoption, cross-jurisdictional rule synthesis capability, andproactive engagement with regulatory sandboxes. Our results reveal a strong, statistically significant positive correlation between an audit firm’s RIQ score and keyquality proxies, including audit report lag reduction, lower incidence of post-auditregulatory findings, and enhanced predictive value of audit opinions for financialstability. Crucially, the study finds that technological integration—specifically theuse of AI for continuous regulatory monitoring and blockchain for immutable audittrail verification—acts as a powerful moderator, amplifying the effect of traditionaldeterminants like experience and size. The paper concludes that in hyper-regulatedenvironments, audit quality is increasingly defined by adaptive, anticipatory capabilities rather than static compliance, necessitating a paradigm shift in how auditfirms are evaluated and how audit quality is conceptualized and assured.